Die Anbahnung einer forschenden Grundhaltung im Verlauf des Praxissemesters: Entwicklungsverläufe und Gelingensbedingungen - Homt, Martina; van Ophuysen, Stefanie

Elternsorgen und Kindersorgen während der Corona-Pandemie - Sander, Andreas; van Ophuysen, Stefanie; Schäfer, Laura; Homt, Martina

Forming Simulation of Tailored Press Hardened Parts - Triebus, Marcel; Reitz, Alexander; Grydin, Olexandr; Grenz, Julian; Schneidt, Andreas; Erhardt, Rüdiger; Tröster, Thomas; Schaper, Mirko (13th European LS-DYNA Conference 2021)

Steigerung der Prognosegüte mechanischer Fügeprozesssimulationen durch den Einsatz einer fügespezifischen Reibmodellierung basierend auf einer experimentellen Parametrisierung - Rossel, Moritz Sebastian; Meschut, Gerson (11. Fügetechnisches Gemeinschaftskolloquium)

Motivationsregulationsformen zum Erwerb pädagogisch-psychologischer Theorien und Befunde im Lehramtsstudium - Grosser, Christine; Wehde, Janis

Die Reflexion der eigenen Lehrtätigkeit von Studierenden in Praxisphasen durch Forschendes Lernen: Prädiktiver Einfluss subjektiver Normen im schulischen und universitären Kontext - Wehde, Janis; Bloh, Bea

Fiber response to pin penetration in dry woven fabric using numerical analysis - Droß, M.; Heyser, Per; Meschut, Gerson; Hürkamp, A.; Dröder, K. (Journal of Advanced Joining Processes)

Großserientaugliche induktive Platinenerwärmung für den Warmformprozess - Tröster, Thomas; Pfeifer, Florian; Nacke, Bernard; Dietrich, André

Kollektive Reflexionsphasen - Bloh, Thiemo

IT-Systeme für das Krisenmanagement - Pottebaum, Jens; Schäfer, Christina (Sicherheitskritische Mensch-Computer-Interaktion)

Die Zukunft sicherheitskritischer Mensch-Computer-Interaktion - Reuter, Christian; Aal, Konstantin; Beham, Frank; Boden, Alexander; Brauner, Florian; Fiedrich, Frank; Fuchs-Kittowski, Frank; Geisler, Stefan; Gennen, Klaus; Herrmann, Dominik; Kaufhold, Marc-André; Klafft, Michael; et al. (Sicherheitskritische Mensch-Computer-Interaktion)

Supporting Innovation Management for SMEs: A Tool for Idea Selection - Gräßler, Iris; Koch, Anna-Sophie; Thiele, Henrik; Dattner, Michael (Proceedings of the ISPIM Innovation Conference)
In innovation management, usually there is a large number of product ideas, not all of which meet the requirements of a company and make sense to pursue further. For selecting the most promising ideas, several methods exist which each focus on a certain aspect. Due to the characteristics of Small and Medium Enterprises (SMEs) such as limited resources, these enterprises have special requirements on methods for selecting ideas. In this study, criteria of SMEs for idea selection are deducted from SME-characteristics. Methods for idea selection are tested for fulfillment of these criteria and the results are combined in a matrix. Together with a guideline, a tool for idea selection in innovation management of SMEs is developed. The results are validated in the context of innovation management in SMEs. By selecting a method, a SME is enabled to make economically viable decisions for their product portfolio, thus ensuring sustainable economic success.
Keywords: innovation management; SME; evaluation method; idea selection; meta-study; idea evaluation

Produktspezifische Optimierung der Nachhaltigkeit im Ersatzteilmanagement. Ganzheitliche Vorgehensweise zur Bewertung der Nachhaltigkeit additiv gefertigter Komponenten für den Aftermarket - Gräßler, Iris; Hillebrand, Stefan; Thiele, Henrik (Digitalisierung im Kontext von Nachhaltigkeit und Klimawandel)
Um der ansteigenden Erderwärmung entgegenzuwirken, erheben immer mehr Regierungen Steuern und Strafzahlungen auf den CO2-Ausstoß. Dieses betrifft auch die Ersatzteil¬versorgung im Automobilbereich. Dabei muss bislang dem Bedarf vorgelagert produziert werden, was mit hohen Lagerkapazitäten und logistischen Aufwänden verbunden ist. CO2-Einsparungen sind daher durch einen Wechsel auf die additive on-demand-Fertigung über ein dezentrales Fertigungsnetzwerk aus Lohndienstleistern möglich. Allerdings ist die dezentrale Ersatzteilfertigung trotz Einbezug des CO2-Preises nicht in jedem Fall wirtschaftlich. Der Grund hierfür liegt in der Abhängigkeit der Gesamtkosten von Faktoren wie Bauteilgeometrie, Logistikaufwand und Stückzahl. Im vorliegenden Beitrag wird eine Vorgehensweise für den Vergleich einer zentralen mit einer dezentralen Ersatzteilversorgung durch die Ergänzung relevanter, produktspezifischer Kennwerte für die additive Bauteilfertigung beschrieben. Neben der Ökobilanz berücksichtigt die entwickelte Methode die wirtschaftliche Rentabilität des Herstellungsverfahrens. Die Validierung dieser Vorgehensweise erfolgt in Kooperation mit einem deutschen Automobilhersteller. Die entwickelte Vorgehensweise dient Automobilherstellern als Entscheidungsunterstützung bei der Fragestellung, ob einzelne Ersatzteilkomponenten herkömmlich oder additiv gefertigt werden.

Should I stay or should I go? The dark side of corporate entrepreneurship - Tomin, Slawa; Krebs, Benjamin (Frontiers of Entrepreneurship Research)

HRM in the Germanic context - Krebs, Benjamin; Wach, Bernhard Alexander; Wehner, Marius Claus; Reichel, Astrid; Mayrhofer, Wolfgang; Sender, Anna; Staffelbach, Bruno; Ligthart, Paul (Handbook on contextual approaches to human resource management)

Aus der Forschung in die Anwendung - Materialqualifizierung im Kunststoff Freiformen - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Kunststoffland NRW report)

Fluid Dynamics of the Open Port Interface for High-Speed Nanoliter Volume Sampling Mass Spectrometry - Liu, Chang; Van Berkel, Gary J.; Kovarik, Peter; Perot, J. Blair; Inguva, Venkatesh; Covey, Thomas R. (Analytical Chemistry)

Analyzing Approximate Value Iteration Algorithms - Ramaswamy, Arunselvan; Bhatnagar, Shalabh (Mathematics of Operations Research (to appear))

Automated Detection of Side Channels in Cryptographic Protocols: DROWN the ROBOTs! - Drees, Jan Peter; Gupta, Pritha; Hüllermeier, Eyke; Jager, Tibor; Konze, Alexander; Priesterjahn, Claudia; Ramaswamy, Arunselvan; Somorovsky, Juraj (14th ACM Workshop on Artificial Intelligence and Security)

Deep Q-Learning: Theoretical Insights from an Asymptotic Analysis - Ramaswamy, Arunselvan; Hüllermeier, Eyke (IEEE Transactions on Artificial Intelligence (to appear))

Weiterentwicklung von GITBlow für dünnwandige Hohlstrukturen auf Organoblechen - Moritzer, Elmar; Kröker, Michael (CU reports)

Simulative analysis of the filling process in the 2K GITBlow process on organo sheets - Moritzer, Elmar; Kröker, Michael

Validation of an Online State Estimation Concept for Microscopic Traffic Simulations◆ - Malena, Kevin; Link, Christopher; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (2021 IEEE Transportation Electrification Conference & Expo (ITEC))
This paper deals with a novel method for the online fitting of a microscopic traffic simulation model to the current state of a real world traffic area. The traffic state estimation is based on limited data of different measurement sources and guarantees general accordance of reality and simulation in terms of multimodal road traffic counts and vehicle speeds. The research is embedded in the challenge of improving the traffic by controlling the traffic light systems (TLS) of the examined area. Therefore, the current traffic state and the predicted route choices of individual road users are the matter of interest. The concept is generally transferable to any road traffic system. To give an impression of the accuracy and potential of the approach, the validation and first application results are presented.

Einfluss eines beheizten Bauraums auf die Schweißnahtqualität - Moritzer, Elmar; Wächter, Julian (Plastverarbeiter)

Tensor-based computation of metastable and coherent sets - Nüske, Feliks; Gelß, Patrick; Klus, Stefan; Clementi, Cecilia (Physica D: Nonlinear Phenomena)

Symmetric and antisymmetric kernels for machine learning problems in quantum physics and chemistry - Klus, Stefan; Gelß, Patrick; Nüske, Feliks; Noé, Frank (Machine Learning: Science and Technology)

Pulverherstellung und Verrundung neuer Polymermaterialien für das selektive Lasersintern (SLS) - Poster - Ponusamy, SathishKumar

A model for the carbon fiber breakage along the twin‐screw extruder - Malatyali, Hatice; Schöppner, Volker; Rabeneck, Nils; Hanselle, Felix; Austermeier, Laura; Karch, David (SPE Polymers)

The Influence of Process Conditions on the Fiber Length Reduction for Recycled Carbon Fibers - Malatyali, Hatice; Schöppner, Volker; Lochbaum, Ella; Bomm, Igor; Hanselle, Felix (SPE ANTEC)

Reproducibility analysis of fiber length measurements during processing with twin screw extruders - Malatyali, Hatice; Schöppner, Volker; Akar, Seyit Ali; Hanselle, Felix; Austermeier, Laura (SPE ANTEC)

The Hare and the Hedgehog: Empirical evidence on the relationship between the individual Pace of Life and the speed-accuracy continuum - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (PloS one)

The relationship between talent management and individual and organizational performance - Krebs, Benjamin; Wehner, Marius Claus (The Routledge companion to talent management)

Lebensdauer vorhersagen? - Gevers, Karina; Schöppner, Volker (K-Zeitung)
Keywords: Infrarotschweißen; Glasfaserverstärkte Kunststoffe; Lebensdauer; Langzeitbelastung

Heated tool butt welding of two different materials – Established methods versus artificial intelligence - Gevers, Karina; Schöppner, Volker; Hüllermeier, Eyke

Development of scale up rules for quasi-simultaneous laser transmission welding of thermoplastics - Arndt, Theresa; Schöppner, Volker

Design and Experimental Investigation of an Additively Manufactured PMSM Rotor - Urbanek, Stefan; Pauline, Frey; Magerkohl, Sebastian; Zimmer, Detmar; Tasche, Lennart; Schaper, Mirko; Ponick, Bernd
Keywords: Elektromotor; Elektromaschine; Additive Fertigung; AF; AM; Additive Manufacturing; DMRC; KAt

3D-Druck in der industriellen Anwendung - Funktions- und fertigungsgerechte Konstruktion mit additiver Fertigung (Vortrag) - Magerkohl, Sebastian; Brüggemann, Jan-Peter

DEVELOPMENT OF A NEW METHOD TO EVALUATE THE DISTRIBUTIVE MIXING QUALITY BASED ON THE PARTICLE TRACKING METHOD AND THE DELAUNAY TRIANGULATION - Frank, Maximilian; Schöppner, Volker (ANTEC® 2021)

Influence of angled dispersion gas on coaxial atomization, spray and flame formation in the context of spray-flame synthesis of nanoparticles - Bieber, M.; Al-Khatib, M.; Fröde, F.; Pitsch, H.; Reddemann, M. A.; Schmid, H-J.; Tischendorf, R.; Kneer, R. (Experiments in Fluids)
Liquid atomization determines the initial conditions for flame formation and particle synthesis. Without a stable flame, high droplet velocities and thus short droplet residence time in the flame may lead to droplets being injected into an extinguished flame, which influences synthesis and final particle output. An experimental investigation of spray formation and flame stability is performed through high-speed visualization. Targeted variation of nozzle geometry is applied to improve spray-flame interaction and compared to a standardized burner. Timescales of spray density and flame fluctuations are quantified and compared, where the latter were significantly larger and hence not correlated. Instead, dispersion gas forms a barrier between spray phase and pilot flame; hence, ignition depends on large liquid lumps with high radial momentum to break through the dispersion gas for spray ignition. Angling of dispersion gas flow increases radial shear and turbulence and leads to refined atomization and improved flame stability. To investigate the nozzle influence on particle formation, particle characteristics are examined by online and offline analytics with focus on particle structures and product purity. The modified nozzle produced smaller primary particle sizes, thus indicating a sensitivity of sintering dominance on the nozzle geometry. Impurities impact the examination of particle structures and general particle functionality. Carbon contamination was apparent in synthesized particles and also indicated sensitivity to nozzle geometry. Discrepancies to literature data are discussed regarding differences in flame activity and droplet characteristics. The report highlights, how product characteristics can differ crucially due to changes in nozzle geometry despite comparable operating conditions.

Separation of Multi-Component Parts for Mechanical Recycling – An Approach to Produce Hard-Soft Combinations with a Better Recyclability - Hopp, Matthias; Mühlhoff, Frederik Marvin (79th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Transitioning to Condition-Based Maintenance on the Distribution Grid: Deriving Design Principles from a Qualitative Study - zur Heiden, Philipp; Priefer, Jennifer (Pre-Conference 16th International Congress on Wirtschaftsinformatik at Universität Duisburg-Essen)

Constructions of a National Threat: Contextualising the Rhetorical Management of the COVID-19 Pandemic in Britain - Tönnies, Merle (Mentalities and Materialities: Essays in Honour of Jürgen Kamm)

Faster, harder, greener? Empirical evidence on the role of the individual Pace of Life for productivity and pro-environmental behavior - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (Ecological Economics)

Kleine Tropfen, große Wirkung - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Kunststoffe)

Assessment of AlZnMgCu alloy powder modification for crack-free laser powder bed fusion by differential fast scanning calorimetry - Zhuravlev, Evgeny; Milkereit, Benjamin; Yang, Bin; Heiland, Steffen; Vieth, Pascal; Voigt, Markus; Schaper, Mirko; Grundmeier, Guido; Schick, Christoph; Kessler, Olaf (Materials & Design)
Additive manufacturing, e.g. by laser powder bed fusion (LPBF), is very attractive for lightweight constructions, as complex and stress-optimised structures integrating multiple functions can be produced within one process. Unfortunately, high strength AlZnMgCu alloys tend to hot cracking during LPBF and thus have not so far been applicable. In this work the melting and solidification behaviour of AlZnMgCu alloy powder variants with particle surface inoculation was analysed by Differential Fast Scanning Calorimetry. The aim is to establish a method that makes it possible to assess powder modifications in terms of their suitability for LPBF on a laboratory scale requiring only small amounts of powder. Therefore, solidification undercooling is evaluated at cooling rates relevant for LPBF. A method for the temperature correction and normalisation of the DFSC results is proposed. Two ways of powder modification were tested for the powder particles surface inoculation by titanium carbide (TiC) nanoparticles: via wet-chemical deposition and via mechanical mixing. A low undercooling from DFSC correlates with a low number of cracks of LPBF-manufactured cubes. It appears that a reduced undercooling combined with reduced solidification onset scatter indicates the possibility of crack-free LPBF of alloys that otherwise tend to hot cracking.
Keywords: Aluminium alloy 7075; Differential fast scanning calorimetry; Solidification; Undercooling; Additive manufacturing

I-AID: Identifying Actionable Information From Disaster-Related Tweets - M. Zahera, Hamada; Jalota, Rricha; Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (IEEE Access)

Knowledge Graphs - Hogan, Aidan; Blomqvist, Eva; Cochez, Michael; d'Amato, Claudia; de Melo, Gerard; Gutiérrez, Claudio; Kirrane, Sabrina; Emilio Labra Gayo, José; Navigli, Roberto; Neumaier, Sebastian; Ngonga Ngomo, Axel-Cyrille; Polleres, Axel; et al. (ACM Comput. Surv.)

Attention to diversity in German CLIL classrooms: Multi-perspective research on students’ and teachers’ perceptions - Siepmann, Philipp; Rumlich, Dominik; Matz, Frauke; Römhild, Ricardo (International Journal of Bilingual Education and Bilingualism)

Bilingualer Unterricht. Aktuelle Herausforderungen und neue Chancen (Fremdsprachen Lehren und Lernen)

Freies Format 2: Nachwuchs-Café (reloaded): Auf dem Weg zur Professur... - Rumlich, Dominik; Matz, Frauke; Juchem-Grundmann, Constanze (Sprache, Kulturen, Identitäten : Umbrüche durch Digitalisierung: 28. Kongress der Deutschen Gesellschaft für Fremdsprachenforschung. Würzburg, 25.-28. September 2019)

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)

Exploring intensity-dependent modulations in EEG resting-state network efficiency induced by exercise - Büchel, Daniel; Sandbakk, Øyvind; Baumeister, Jochen (European Journal of Applied Physiology)
Abstract Purpose Exhaustive cardiovascular load can affect neural processing and is associated with decreases in sensorimotor performance. The purpose of this study was to explore intensity-dependent modulations in brain network efficiency in response to treadmill running assessed from resting-state electroencephalography (EEG) measures. Methods Sixteen trained participants were tested for individual peak oxygen uptake (VO 2 peak ) and performed an incremental treadmill exercise at 50% (10 min), 70% (10 min) and 90% speed VO 2 peak (all-out) followed by cool-down running and active recovery. Before the experiment and after each stage, borg scale (BS), blood lactate concentration (B La ), resting heartrate (HR rest ) and 64-channel EEG resting state were assessed. To analyze network efficiency, graph theory was applied to derive small world index (SWI) from EEG data in theta, alpha-1 and alpha-2 frequency bands. Results Analysis of variance for repeated measures revealed significant main effects for intensity on BS, B La , HR rest and SWI. While BS, B La and HR rest indicated maxima after all-out, SWI showed a reduction in the theta network after all-out. Conclusion Our explorative approach suggests intensity-dependent modulations of resting-state brain networks, since exhaustive exercise temporarily reduces brain network efficiency. Resting-state network assessment may prospectively play a role in training monitoring by displaying the readiness and efficiency of the central nervous system in different training situations.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.

Beratung bei Studienzweifel als Instrument des Qualitätsmanagements von Studium und Lehre - Sloane, Hannah; Mauer, Eileen (Ursprünge hinterfragen - Vielfalt ergründen - Praxis einordnen)

Quantifying the coupling strength of adhesively bonded materials by investigating mode repulsion regions - Zeipert, Henning; Johannesmann, Sarah; Nicolai, Marcel; Lugovtsova, Yevgeniya; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2021)

Ansätze zur Diagnose und Förderung von Problemlösefähigkeiten in der Studieneingangsphase Physik - Lahme, Simon; Bauer, Anna; Reinhold, Peter (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung)

IN OTHER WORDS: A NAIVE APPROACH TO TEXT SPINNING - Bäumer, Frederik Simon; Kersting, Joschka; Denisov, Sergej; Geierhos, Michaela (PROCEEDINGS OF THE INTERNATIONAL CONFERENCES ON WWW/INTERNET 2021 AND APPLIED COMPUTING 2021)
Content is the new oil. Users consume billions of terabytes a day while surfing on news sites or blogs, posting on social media sites, and sending chat messages around the globe. While content is heterogeneous, the dominant form of web content is text. There are situations where more diversity needs to be introduced into text content, for example, to reuse it on websites or to allow a chatbot to base its models on the information conveyed rather than of the language used. In order to achieve this, paraphrasing techniques have been developed: One example is Text spinning, a technique that automatically paraphrases text while leaving the intent intact. This makes it easier to reuse content, or to change the language generated by the bot more human. One method for modifying texts is a combination of translation and back-translation. This paper presents NATTS, a naive approach that uses transformer-based translation models to create diversified text, combining translation steps in one model. An advantage of this approach is that it can be fine-tuned and handle technical language.
Keywords: Software Requirements; Natural Language Processing; Transfer Learning; On-The-Fly Computing

Szenario-Technik mit digitalen Technologien (in Druck) - Ködding, Patrick; Dumitrescu, Roman (Digitalisierung souverän gestalten)

Improving the Accuracy of Deep Drawn Fiber-Metal Laminate Parts by Preliminary Surface Treatment - Voswinkel, Dietrich (IOP Conference Series: Materials Science and Engineering)

Towards the Concept of a Digital Green Twin for a Sustainable Product Lifecycle - Michael, Jan; Grote, Eva-Maria; Pfeifer, Stefan; Rasor, Rik; Henke, Christian; Trächtler, Ansgar; Kaiser, Lydia

Improving the Accuracy of Deep Drawn Fiber-Metal Laminate Parts by Preliminary Surface Treatment - Voswinkel, Dietrich; Sapli, Hüseyin; Kloidt, Dennis; Heggemann, Thomas; Homberg, Werner; Grydin, Olexandr; Schaper, Mirko (IOP Conference Series: Materials Science and Engineering)

General analytic theory of classical collinear three-wave mixing in a monolithic cavity - Santandrea, Matteo; Stefszky, Michael; Silberhorn, Christine (Journal of Optics)

Materials Screening for Disorder‐Controlled Chalcogenide Crystals for Phase‐Change Memory Applications - Xu, Yazhi; Wang, Xudong; Zhang, Wei; Schäfer, Lisa; Reindl, Johannes; vom Bruch, Felix; Zhou, Yuxing; Evang, Valentin; Wang, Jiang‐Jing; Deringer, Volker L.; Ma, En; Wuttig, Matthias; et al. (Advanced Materials)

Towards the Concept of a Digital Green Twin for a Sustainable Product Lifecycle - Michael, Jan; Grote, Eva-Maria; Pfeifer, Stefan Achilles; Rasor, Rik; Henke, Christian; Trächtler, Ansgar; Kaiser, Lydia (Proceedings of the 1st International Conference on Water Energy Food and Sustainability (ICoWEFS 2021))

Kooperation und Praxiskompetenz - Bloh, Thiemo

Practical approach for the development of digital guidelines for smart cities - Förster, Magdalena; Rabe, Martin; Kühn, Arno; Dumitrescu, Roman (Proceedings of the IEEE E-TEMS 2021)

The Paradigm of Design Thinking and Systems Engineering in the Design of Cyber-Physical Systems: A Systematic Literature Review - Tekaat, Julian; Anacker, Harald; Dumitrescu, Roman (Proceedings of the 7th IEEE International Symposium on Systems Engineering)

Need for Action for a Company-Wide Introduction of Systems Engineering in Machinery and Plant Engineering - Wilke, Daria; Schierbaum, Anja; Kaiser, Lydia; Dumitrescu, Roman (Proceedings of the International Conference on Engineering Design, ICED 2021)

Augmented Reality-based Product Validation to Support Collaborative Engineering of Complex Technical Systems - Eckertz, Daniel; Anacker, Harald; Dumitrescu, Roman (Proceedings of the 18th International Conference on Remote Engineering and Virtual Instrumentation, Online Engineering and Society 4.0)

Increased Prevalence of Subclinical Hypothyroidism and Thyroid Autoimmunity in Depressed Adolescents - Hirtz, Raphael; Focker, Manuel; Libuda, Lars; Antel, Jochen; Ozturk, Dana; Kiewert, Cordula; Munteanu, Martin; Peters, Triinu; Fuhrer, Dagmar; Zwanziger, Denise; Thamm, Michael; Hebebrand, Johannes; et al. (The Journal of Clinical Psychiatry)

Analyzing socio-technical risks in implementation of Industry 4.0-use cases - Gabriel, Stefan; Grauthoff, Tobias; Joppen, Robert; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Rapid amelioration of anorexia nervosa in a male adolescent during metreleptin treatment including recovery from hypogonadotropic hypogonadism - Antel, Jochen; Tan, Susanne; Grabler, Marvin; Ludwig, Christine; Lohkemper, Dominik; Brandenburg, Tim; Barth, Nikolaus; Hinney, Anke; Libuda, Lars; Remy, Miriam; Milos, Gabriella; Hebebrand, Johannes (European Child & Adolescent Psychiatry)
Abstract With this case report we support our medical hypothesis that metreleptin treatment ameliorates starvation related emotional, cognitive and behavioral symptomatology of anorexia nervosa (AN) and show for the first time strong effects in a male patient with AN. A 15.9 year old adolescent with severe AN of eight-month duration was treated off-label with metreleptin. Hyperactivity was assessed with accelerometry. Visual analogue scales (VAS), validated self- and clinician rating scales and lab results tracked changes from baseline to end of the 24-day dosing period and a five-month follow-up. Substantial improvements of mood and eating disorder related cognitions and hyperactivity set in after two days of treatment. During dosing, sub-physiological testosterone and TT3 levels normalized; clinically libido reemerged. Weight did not increase substantially during the dosing period. During follow-up target weight was attained; mood did not deteriorate; hyperactivity ceased. The results substantiate the strong effects seen in female cases and underscore the need for a double-blind placebo-controlled trial to confirm the observed strong, multiple and rapid onset beneficial effects of metreleptin in AN.

Learning context-dependent choice functions - Pfannschmidt, Karlson; Gupta, Pritha; Haddenhorst, Björn; Hüllermeier, Eyke (International Journal of Approximate Reasoning)

Investigation of shear rates in twin-screw extruders using CFD simulations - Malatyali, Hatice; Schöppner, Volker (36th PPS)

Investigation of the influence of process and screw configurations on fiber length distribution for recycled carbon fiber - Malatyali, Hatice; Schöppner, Volker; Hoemann, Theresa (36th PPS)

Analysis and modelling of the material degradation of polypropylene on the co-rotating twin-screw extruder - Altepeter, Matthias; Schöppner, Volker; Wanke, Sven

Befähigung zur Reflexion und zum Umgang mit Ambiguitäten. Zur Wirksamkeit von Unterricht für "Lebensführung" - Schlegel-Matthies, Kirsten; Wespi, Claudia (Wirksamer Fachunterricht. Eine metaanalytische Betrachtung von Expertisen aus 17 Schulfächern)

Wirksamer Unterricht für Lebensführung. (Unterrichtsqualität: Perspektiven von Expertinnen und Experten 12) - Schlegel-Matthies, Kirsten; Wespi, Claudia

Mechanisches Fügen von FKV-FKV-Verbindungen - Han, Daxin; Meschut, Gerson
Within the scope of the research project, four new mechanical joining processes for the singlestage, pre-hole-free joining of FRP-FRP joints were further developed. For this purpose, the joining processes under consideration were first implemented on existing equipment at the research institute. Based on the successful adaptation of the joining processes, characteristics of the joints were documented by means of micrographs and observation of external characteristics, on the basis of which measures for process modification were derived. The process modifications were carried out on a process-specific basis for a selected GFRPGFRP joint. The aim was to improve the joint quality, in particular with regard to the reduction of laminate damage, by means of targeted element and tool development in addition to the increase in process stability. Based on these results, a realistic suitability evaluation of the joining methods was carried out with regard to process and manufacturing flexibility. As a result, two self-piercing riveting processes, which showed the greatest suitability potential, were examined in more detail to analyse the application limits. In the process, the joints were sampled on further material combinations with varied fibre and matrix systems. In addition, joints with adhesive were investigated, in which the influence of the adhesive viscosity on the joint properties was analysed. The joint properties of the new joining method were then comprehensively determined by tensile tests under quasi-static, cyclic loads. Finally, the behaviour of the optimised joints under corrosive load was characterised in the salt spray test. Through the targeted process modifications in this project, the FRP-FRP joints can be joined with less damage, enabling improved joint quality in the FRP-based components.

Quellen der Selbstwirksamkeitsüberzeugung von Grundschullehrkräften im Kontext inklusiver Erziehung und Bildung - Franzen, Katja

The concept of a digital twin and its potential for learning organizations - Berisha-Gawlowski, Angelina; Caruso, Carina; Harteis, Christian (Digital transformation of learning organizations)

Die Forderung nach Lebenslangem Lernen: Zwischen Banalität, Herausforderung und Zumutung - Harteis, Christian (Lebenslanges Lernen in der Musikpädagogik. Theorie und Praxis)

Erklärungsfaktoren für Handlungsintentionen von Lehrkräften an inklusiven und nicht-inklusiven Grundschulen bei der Gestaltung von adaptivem Unterricht. - Löper, Marwin Felix; Hellmich, Frank (Empirische Pädagogik)

The role of students’ experiences in attitude formation towards peers with non-compliant classroom behaviour in inclusive primary schools - Löper, Marwin Felix; Schwab, Susanne; Lehofer, Mike; Hellmich, Frank (European Journal of Special Needs Education)

Erweiterung des epistemologischen Verständnisses durch Konfrontation mit anomalen Daten. - Pollmeier, Pascal; Fechner, Sabine (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch?)

Guaranteeing Properties of Reconfigurable Hardware Circuits with Proof-Carrying Hardware - Wiersema, Tobias
Previous research in proof-carrying hardware has established the feasibility and utility of the approach, and provided a concrete solution for employing it for the certification of functional equivalence checking against a specification, but fell short in connecting it to state-of-the-art formal verification insights, methods and tools. Due to the immense complexity of modern circuits, and verification challenges such as the state explosion problem for sequential circuits, this restriction of readily-available verification solutions severely limited the applicability of the approach in wider contexts. This thesis closes the gap between the PCH approach and current advances in formal hardware verification, provides methods and tools to express and certify a wide range of circuit properties, both functional and non-functional, and presents for the first time prototypes in which circuits that are implemented on actual reconfigurable hardware are verified with PCH methods. Using these results, designers can now apply PCH to establish trust in more complex circuits, by using more diverse properties which they can express using modern, efficient property specification techniques.
Keywords: Proof-Carrying Hardware; Formal Verification; Sequential Circuits; Non-Functional Properties; Functional Properties

Morphological Dynamics of Leukemia Cells on TiO2 Nanoparticle Coatings Studied by AFM - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Grundmeier, Guido; Camargo Amado, Ruben Jesus; Keller, Adrian (Applied Sciences)
Coatings of modified TiO2 nanoparticles (TiO2-m) have been shown to effectively and selectively trap non-adherent cancer cells, with an enormous potential for applications in photodynamic therapy (PDT). Leukemia cells have a remarkable affinity for TiO2-m coatings, adhering to the surface by membrane structures and exhibiting morphologic characteristics of amoeboid locomotion. However, the details of the cell–substrate interaction induced by the TiO2-m coating remain elusive. With the aim to obtain a better understanding of this phenomenon, leukemia cell adhesion to such coatings was characterized by atomic force microscopy (AFM) for short contact times up to 60 min. The cell and membrane morphological parameters mean cell height, contact area, cell volume, and membrane roughness were determined at different contact times. These results reveal cell expansion and contraction phases occurring during the initial stage of adhesion. Subsequently, the leukemic cells reach what appears to be a new resting state, characterized by pinning of the cell membrane by TiO2-m nanoparticle aggregates protruding from the coating surface.

Towards generative design in the development of mechatronic integrated devices (MID) - Kharatyan, Aschot; Jürgenhake, Christoph; Dumitrescu, Roman (Procedia CIRP)

Approach for a modular design methodology for an efficient development of 3D MID components - Mager, Thomas; Jürgenhake, Christoph; Dumitrescu, Roman (14th International Congress Molded Interconnect Devices (MID))

Evaluation of different additive manufacturing technologies for MIDs in the context of smart sensor systems for retrofit applications - Hemmelgarn, Florian; Ehlert, Patrick; Mager, Thomas; Jürgenhake, Christoph; Dumitrescu, Roman (14th International Congress Molded Interconnect Devices (MID))

Socio-technical risk management in the age of digital transformation – identification and analysis of existing approaches - Menzefricke, Jörn Steffen; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Identification of Socio-Technical Risks and Their Correlations in the Context of Digital Transformation for the Manufacturing Sector - Schnasse, Felix; Menzefricke, Jörn Steffen; Dumitrescu, Roman (Proceedings of the IEEE 8th International Conference on Industrial Engineering and Applications (ICIEA))

SAVE: Security & safety by model-based systems engineering on the example of automotive industry - Japs, Sergej; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)

Erfolgspotentiale für die Zukunft des Engineeringstandorts Deutschland – Ein Beitrag zum Advanced Systems Engineering - Dumitrescu, Roman; Anacker, Harald; Grote, Eva-Maria; Rasor, Rik; Tekaat, Julian; Meyer, Maurice; Gausemeier, Jürgen; Steglich, Steffen (Vorausschau und Technologieplanung - 16. Symposium Vorausschau und Technologieplanung)

Metamodel for safety and security integrated system architecture modeling - Kharatyan, Aschot; Tekaat, Julian; Japs, Sergej; Anacker, Harald; Dumitrescu, Roman (Proceedings of the Design Society)

UNDERSTANDING USAGE DATA-DRIVEN PRODUCT PLANNING: A SYSTEMATIC LITERATURE REVIEW - Meyer, Maurice; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract Cyber-physical systems (CPS) are able the collect huge amounts of data about themselves, their users, and their environment during their usage phase. By feeding these usage data back into product planning, manufacturers can optimize their engineering and decision-making processes. Despite promising potentials, most manufacturers still do not analyze usage data within product planning. Also, research on usage data-driven product planning is scarce. Therefore, this paper aims to identify the main concepts, advantages, success factors and challenges of usage data-driven product planning. To answer the corresponding research questions, a comprehensive systematic literature review is conducted. From its results, a detailed description of usage data-driven product planning consisting of six main concepts is derived. Furthermore, taxonomies for the advantages, success factors and challenges of usage data-driven product planning are presented. The six main concepts and the three taxonomies allow for a deeper understanding of the topic while highlighting necessary future actions and research needs.

Zukunftsrobuste Weiterentwicklung von Produktportfolios: Erkenntnisse und Handlungsbedarfe aus der Praxis - Meyer, Maurice; Hemkentokrax, Jan-Philipp; Koldewey, Christian; Dumitrescu, Roman; Tröster, Peter M.; Schlegel, Michael; Kling, Christopher L.; Rapp, Simon; Albers, Albert (Vorausschau und Technologieplanung - 16. Symposium Vorausschau und Technologieplanung)

Towards Identifying Data Analytics Use Cases in Product Planning - Meyer, Maurice; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Die Kraft von Startup-Partnerschaften für das Innovationssystem eines Automobilzulieferers - Hemkentokrax, Jan-Philipp; Eckelt, Daniel; Haarmann, Lennard; Koldewey, Christian; Dumitrescu, Roman (Vorausschau und Technologieplanung - 16. Symposium Vorausschau und Technologieplanung)